Menguji Keberterimaan Pemikiran Tentang “Monogami Sebagai Syarat Tak Tertulis Saat Pernikahan Berlangsung” Menurut Para Ahli Hukum Islam Di Sumatera Utara - Nur Aisah Simamora (Jurnal Penelitian Medan Agama, 2019)
Most of the arguments of polygamy have only explained the reason for the ability, for example, "Polygamy is clearly a word in the Koran, therefore, the issue of polygamy is not disputed!", "Prophet SAW. And the majority of his companions are polygamous, and they are the main role models in practicing this religion ", where the answers like the above do not satisfy many parties, especially for women. There are at least two aspects that have not been accommodated in the above answer, to address very serious problems such as polygamy. First, the aspects of women's feelings and their rights have not been touched in the answers above. Second, the reasoning aspect of consideration of the situation and condition that is the study of jurisprudence method integrated with the study of the sharia Maqashid. The answers like the above are still limited textual reasoning which is a study usul fikih, where when viewed to the verse that allows polygamy alone, then the law that can be withdrawn from it is the legal polygamy of Mubah. But solving a legal problem using a Qur'anic verse alone regardless of other verses and does not consider the situation and psychological conditions of society, anthropological, cultural, and social.